Confidence in Justice and Police in Latin America: Analysis of the Effects of Criminal Justice Reform (1995-2013) - Oyanedel, Juan Carlos (Revista del CLAD Reforma y Democracia, 2016)
The study analyzes the effect of criminal justice reform in confidence in justice and police in Latin America, since 1995 to 2013. This research question is relevant given the legitimate problems inherited by military governments in the region. In order to answer this question, first, a brief framework about legal system in Latin America is presented. Then, criminal justice reforms are exposed, emphasizing in similarities and difference among the countries in this region. According to these characteristics, a conceptual cluster is proposed, which is include to test the influence of criminal justice reform in confidence in justice and police. After that, a conceptual framework about justice legitimate and procedural justice is presented, which allows to establish the major hypothesis of this study: criminal justice reform leads to higher rates of confidence in justice and police. Using data from Latinobarometer survey (1995-2013), in 18 countries from Latin America, results show that low and medium reach of the reforms are associated with higher rates of confidence, controlling the effect of some possible confounders. Finally, the article discusses the results and emphasizes the relevance of the moderation in the introduction of reforms in justice issues.
Keywords: Justice Administration; Judicial Reform; Procedural Law; Penal Law, Police; Legitimacy; Latin America